307Clinical outcomes of pacing induced cardiomyopathy in patients with preserved left ventricular systolic function and atrioventricular block. (18th June 2020) - Dor, O; Haim, M; Barrett, O; Novack, V; Konstantino, Y
Abstract: Funding Acknowledgements: None Background: Patients with preserved LVEF and atrioventricular block (AVB) who are anticipated for high-burden of right ventricular (RV) pacing possess a risk to develop pacing induced cardiomyopathy (PICM). Aims: To evaluate the incidence and outcomes of RV-PICM in this patient"s population. Methods: 1013 patients with AVB underwent first time pacemaker (PM) implantation between 2002 and 2016. A total of 203 patients with normal LVEF were included. Follow-up echocardiography was examined for a decrease in LVEF > 10%. Alternative causes for cardiomyopathy were excluded. Patient"s characteristics, mortality and hospitalizations for heart failure (HF) were compared between the PICM and non-PICM groups. Results: 51 patients (25%) developed PICM, with 22 patients (11%) showing LVEF < 40%. During mean follow-up of 49.2 months, the risk of HF hospitalization or all-cause mortality was significantly higher in the PICM group (35.3% vs. 19.1%, p = 0.009). LVEDD was independently associated with PICM (HR = 1.10, 95% CI: 1.03-1.17, p = 0.01) and CAD was nearly associated with PICM (HR = 2.19, 95% CI: 0.98-4.90, p = 0.06). Conclusions: The incidence of PICM in patients with normal LVEF and AVB is alarmingly high. PICM in patients with a previously normal LVEF is associated with unfavorable outcomes.